POLAR BINARIES IN SHONA PATEL’S TEATIME FOR THE FIREFLY - S Sandhya; Bose, R. David Raja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Polar binaries are opposite ideas shaping a narrative. This paper seeks to examine the polar binaries found in Shona Patel’s novel Teatime for the Firefly. Three pairs of polar binaries find place in the novel – tradition vs. modernity; authority vs. resistance; and eastern vs. western ideologies. The protagonist Layla defies superstitions and gender expectations, embracing education and independence. The central character, Dadamoshai, is an amalgamation of tradition and modernity. The tea pluckers register protests and resistance against the management. The condition of the tea plantations as one of authority and resistance is highlighted in the novel. The contrast between Eastern and Western ideologies further highlights the divide between preserving native values and embracing foreign influence, particularly in education and societal roles. Through these opposing perspectives, the novel illustrates a shifting world where people must navigate transformation while holding on to their roots.